Impact of California Safe Patient Handling Legislation: Health Care Workers' Perspectives. (March 2021) - Lee, Soo-Jeong; Stock, Laura; Michalchuk, Victoria; Adesoye, Kelsie; Mullen, Kathleen
Background: Musculoskeletal injuries from patient handling are significant problems among health care workers. In California, legislation requiring hospitals to implement safe patient handling (SPH) programs was enacted in 2011. This qualitative study explored workers' experiences and perceptions about the law, their hospital's SPH policies and programs, patient handling practices, and work environment. Methods: Three focus groups were conducted with 21 participants (19 nurses and 2 patient handling specialists) recruited from 12 hospitals located in the San Francisco Bay Area and San Joaquin Valley. Qualitative content analysis was used for data analysis. Results: Multiple themes emerged from diverse experiences and perceptions. Positive perceptions included empowerment to advocate for safety, increased awareness of SPH policies and programs, increased provision of patient handling equipment and training, increased lift use, and improvement in safety culture. Perceived concerns included continuing barriers to safe practices and lift use such as difficulty securing assistance, limited availability of lift teams, understaffing, limited nursing employee input in the safety committee, blaming of individuals for injury, increased workload, and continuing injury concerns. Participants indicated the need for effective training, sufficient staffing, and management support for injured workers. Conclusions/Application to Practice: This study identified improvements in hospitals' SPH programs and practices since the passage of California's SPH law, as well as continuing challenges and barriers to safe practices and injury prevention. The findings provide useful information to understanding the positive impacts of the SPH law but also notes the potential limitations of this legislation in the view of health care workers.